Analisis Pemanfaatan Media Sosial dalam Peningkatan Penjualan Produk Kuliner: Studi Kasus pada Usaha Mf Dessert - Yulisdianti Arafah; Failur Rahman; Edhi Taqwa; Yunus Sading; Musdayanti yanti (ManBiz: Journal of Management and Business, 2024)
Technology is developing very rapidly which has many consequences in the field of human life, especially the development of technology in the field of the internet. As a result of these advancements, trading systems, ways of transacting, and marketing systems will all undergo a revolution. Previously, you had to meet the merchant in person if you wanted to buy something. As a result, the distance between the seller and the buyer is quite short. However, with technological breakthroughs, especially in the realm of the internet, all barriers of distance, time, and cost can be easily overcome. One type of internet technology development that can help build a business is the use of social media. MF Dessert is a business established in 2021 that provides a variety of dessert menus such as Haunted Chocolate, Mille Crepes and Fruit Salad. This study aims to find out the analysis of the use of social media in increasing sales culinary products (case study on MF Dessert business). This study uses a qualitative descriptive approach. The results of the research obtained are that the social media used are WhatsApp, Facebook and Instagram, where the use of Whatsapp is more often used than Facebook and Instagram and MF Dessert's business sales have increased by using social media. In conclusion, the use of social media makes it easier for dessert sales that reach more many consumers and social media that is more often used is WhatsApp, the amount of profit obtained from online sales in November is more than Rp. 170,000 compared to direct/offline sales in October. So that the number of sales of MF Dessert's business increased by using social media.